The new American college town : designing effective campus and community partnerships - Martin, James, 1948 January 14-; Samels, James E. (Johns Hopkins University Press, 2019)
"As colleges and universities become more networked, presidents and provosts have embraced the benefits of collaborative, sustainable town-gown relationships. This edited collection is targeted at leaders on both sides of these conversations, and it presents blueprints for building more collaborative relationships. The book's opening chapter provides an overview of twenty characteristics of the new American college town that the editors developed after listening to and interviewing college town planners, elected officials, and college and university administrators for more than three years. For most of the chapters authored by contributors, the editors invited teams that are currently planning or managing a college town relationship. Almost all chapters also include photographs and sidebars of innovative outreach efforts and partnerships"--